The Effectiveness of Legal Aid Provision at The Makassar District Court - Firmansyah, Muhammad Fiqhi; Syamsuddin, Rahman; Amiruddin, Muh.; Fuady, Muhammad Ikram Nur (Jurnal Mulawarman Law Review, 2024)
This research aims to find out the effectiveness of the legal aid center in the Makassar District Court. The research method used by the author is a type of empirical legal research where the approach used is a sociolegal approach where this research connects the objectives and data obtained in the field and the research location at the Makassar Court Class IA Special as for the data sources used, namely primary, secondary and tertiary data sources. The data collection techniques are observation and interview studies, using research instruments and descriptive data analysis. The discussion is an explanation of the research location and discussion by researchers in conducting interviews with employees and the community. The conclusion of this research is that the application is still lacking, and the opportunity is to help the community more the challenges faced are still many people who lack understanding of legal aid.